Maan-Miehen Huone- ja Koti-Aptheeki - Ganander, Christfrid, 1741-1790 (Salt Lake City, UT : Project Gutenberg, 2024)
"Maan-Miehen Huone- ja Koti-Aptheeki" by Christfrid Ganander is a collection of home remedies and medicinal recipes written in the late 18th century. This work provides practical advice on various treatments for common ailments that can be prepared at home, utilizing both homemade ingredients and those available from apothecaries. The text reflects the medicinal practices of the time, focusing on easily accessible cures for rural communities in Finland. The opening of this work outlines its purpose and utility, emphasizing the need for rural inhabitants, isolated from urban apothecaries, to be able to treat minor illnesses themselves. It introduces the reader to the notion that while many remedies exist, this book specifically aims to simplify their inventory by detailing only the most essential and commonly needed medications. The initial recipes presented include tinctures and ointments made from local herbs and natural ingredients, demonstrating both the author's intent to empower individuals with useful knowledge and the practical applications of folk medicine in everyday life. (This is an automatically generated summary.)
Release date is 2024-12-21
Jari Koivisto
Keywords: Medicine, Popular -- Early works to 1800